Analisis Gaya Kepemimpinan Transformasional Kepala Sekolah Menurut Agama Islam dalam Meningkatkan Mutu Pendidikan - Dea Wanda Milarahma Putri; Mila Alvionita; Salfen Hasri; Sohiron (Cendekia, 2024)
This research aims to determine various ways in which the transformational school principal at SDN 044 Karya Indah can improve the quality of education based on Islamic law. To interpret the phenomena that occur, this research uses a descriptive qualitative research approach to collect data from natural settings. In addition, a case study approach is used to answer questions about how, about, or what is being researched. The data collection technique uses interviews and the data analysis technique uses source triangulation. Based on the research results, the principal of SDN 044 Karya Indah is looking for innovative and creative solutions to school problems referring to Islamic law, such as forming a school committee, increasing the budget to buy textbooks, allowing teachers and employees to work, improving the quality of human resources, and improving school facilities and infrastructure. such as adding study rooms, establishing prayer rooms renovating canteens, and improving the welfare of teachers and employees through increasing honorariums. This is by leaders based on the Koran and Hadith, namely: Justice and Fair Leadership; Commitment to Education; Prudence in Management; Character and Moral Development; Cooperation and Partnership; Sustainability and Innovation; Generosity and Attention to Students.